Low Maternal Serum 25‐Hydroxyvitamin D Concentration Is Associated With Postpartum Hemorrhage: A Retrospective Observational Study - Li, Wei-Jiun; Chen, Kuo-Hu; Huang, Lee-Wen; Tsai, Yieh-Loong; Seow, Kok-Min (Frontiers in Endocrinology, 2022)
Objective: The primary aim of this study is to investigate the relationship between vitamin D serum level and the incidence of postpartum hemorrhage (PPH). The secondary objective is to determine the relative risk of low vitamin D associated with PPH. Methods: This was a retrospective observational study. A total of 600 women who had delivered their babies in a single tertiary teaching hospital were enrolled. Serum blood test for 25(OH)D was performed at 35+0 to 36+6 weeks of pregnancy to measure vitamin D. A 25(OH)D level < 20 ng/mL was defined as vitamin D deficient, and a level 21–29 ng/mL as insufficient. Results: Vitamin D levels were deficient in 145 (24.1%) and insufficient in 254 (42.3%) of the women tested. Women with deficient and insufficient vitamin D levels were significantly younger than those with sufficient vitamin D levels (p < 0.001). The overall rates of PPH in the deficient and insufficient groups were 6.9% and 6.7%, respectively, and were significantly higher than the rate of the normal vitamin D group (1.5%, p = 0.009). Women with sufficient vitamin D levels had significantly higher hemoglobin levels than those with low vitamin D levels. Increased vitamin D levels were associated with a significantly low risk of PPH (AOR: 0.93, CI: 0.89–0.98, p = 0.006). Conclusion: Our results suggest that a low vitamin D level is a risk factor for PPH. Thus, antepartum care should include vitamin D supplements for all women if possible.